A new species of Rock-Dwelling Scinax Wagler (Anura: Hylidae) from Chapada dos Veadeiros, Central Brazil - Araujo-Vieira, Katyuscia; Brandão, Reuber Albuquerque; Faria, Daniele Carvalho Do Carmo (Zootaxa, 2015)
A new species of the Scinax ruber clade is described from Chapada dos Veadeiros region, Central Brazil. The new species is diagnosed by having SVL 21.9–27.7 mm in males and 26.7–31.7 mm in females; snout acuminate in dorsal view and rounded in profile; medium-sized tympanum; vocal sac single, median, subgular, that does not reach the pectoral region; iris iridescent yellow, with some thin, darker reticulations; tadpoles with ventral oral disc; P-3 regular and unmodified as a labial arm; absence of keratinized and colored plates on the sides of the lower jaw-sheath; presence of a keratinized and colored spur on each side behind the lower jaw-sheath; dorsolateral eyes, ventrally invisible; and advertisement call composed of 8–14 notes each with 4–18 pulses, and duration of 290–420 ms. The new species uses temporary creeks in rock meadows above 1.000 m a.s.l. and males calls from rock outcrops. The dorsal color pattern enables this species to camouflage in this kind of surfaces.